A critical role for long-term potentiation mechanisms in the maintenance of object recognition memory in perirhinal cortex revealed by the infusion of zeta inhibitory pseudosubstrate - Outram, Alexandra R.; Brown, Malcolm W.; Warburton, Elizabeth Clea; Barker, Gareth R. I. (Frontiers in Behavioral Neuroscience, 2022)
Object recognition, the ability to discriminate between a novel and a familiar stimulus, is critically dependent upon the perirhinal cortex. Neural response reductions upon repetition of a stimulus, have been hypothesised to be the mechanism within perirhinal cortex that supports recognition memory function. Thus investigations into the mechanisms of long-term depression (LTD) in perirhinal cortex has provided insight into the mechanism of object recognition memory formation, but the contribution of long-term potentiation (LTP) to object recognition memory formation has been less studied Inhibition of atypical PKC activity by, ZIP impairs the maintenance of LTP but not LTD, thus here infusion of ZIP into the perirhinal cortex allowed us to investigate the contribution of LTP-like mechanisms to object recognition memory maintenance. Infusion of ZIP into the perirhinal cortex of rats 24h after the sample phase impaired performance in an object recognition but not an object location task. In addition, performance in a perceptual oddity task, which requires perirhinal cortex function, was not disrupted by ZIP. The impairment in object recognition by ZIP was prevented by administration of the peptide GluA23y, which blocks the endocytosis of GluA2 containing AMPA receptors. Together these results demonstrate the importance of LTP-like mechanisms to the maintenance of object recognition memory in the perirhinal cortex.